After the genocide in Rwanda: humanistic perspectives on social processes of post-conflict posttraumatic growth - Joseph, Stephen (Taylor & Francis, 2018)
The aim was to contribute to an understanding of social processes of post-conflict healing, reconciliation and development, by reflecting on what lessons might be taken from posttraumatic growth research to inform trauma practitioners and researchers in Rwanda. Following a theoretical discussion on the implicit assumptions, limitations and dangers of imposing ideas from Western psychology, it is concluded that we might be best advised to turn to humanistic psychology with its person-centered stance of recognizing that it is the people themselves who will be their own best experts.